Low Pressure UV Photolysis of the Pharmaceutical Compounds Acetaminophen, Atenolol, Bezafibrate, Diclofenac and Ibuprofen - Katsumata, Caroline Pereira; Parizi, Marcela Prado Silva [UNESP]; Lastre-Acosta, Arlen Mabel; Teixeira, Antonio Carlos Silva Costa (MDPI, 2022)
Pharmaceutically active compounds (PhACs) are continuously introduced into the environment by human and livestock excretion, hospital sewage and pharmaceutical effluents. While the performance of UV photolysis regarding PhACs degradation may be limited by low quantum yields, it may be efficient when the contaminants significantly absorb UV radiation. In this work, the direct photolysis under 254 nm UVC radiation of acetaminophen (ACT), atenolol (ATL), bezafibrate (BZF), diclofenac (DIC) and ibuprofen (IBU), isolated and in mixture, was investigated. The results showed that PhAC photolysis followed apparent first-order kinetics, with removals ranging from 32% to 99% after 60 min, while all the compounds exhibited lower photolysis rates when mixed in solution. Less than 13% mineralization was achieved. The toxicity of irradiated solutions of Vibrio fischeri remained the same or slightly decreased for ATL, BZF and IBU, increased for ACT, and notably decreased for DIC; nevertheless, the solution of mixed PhACs became very toxic following irradiation, showing the need for oxidant addition for removing residual toxicity.
Keywords: advanced water treatment; pharmaceutical facility effluents; pharmaceutically active compounds; photolysis; toxicity; wastewater treatment